A relationship between intestinal microbiome and epilepsy: potential treatment options for drug-resistant epilepsy - A. S. Cherednichenko; P. V. Mozdor; T. K. Oleynikova; P. A. Khatam; F. M. Nastueva; K. O. Kovalenkov; A. S. Serdinova; A. Kh. Osmaeva; A. I. Rovchak; Yu. Yu. Esikova; M. Kh. Shogenova; K. I. Akhmedov; et al. (Эпилепсия и пароксизмальные состояния)
Background. According to the World Health Organization, about 50 million people worldwide suffer from epilepsy. Almost 1/3 of patients are diagnosed with drug-resistant epilepsy (DRE). A relationship between intestinal microbiome (IM) and the central nervous system carried out throughout life via bidirectional dynamic network exists. It has been evidenced that IM profile becomes altered in patients with DRE.Objective: to summarize the current literature data on the role for microbiome-gut-brain axis in DRE, as well as to assess an importance of IM composition changes as a prognostic marker for developing DRE.Material and methods. The authors conducted a search for publications in the electronic databases PubMed/MEDLINE and eLibrary, as well as Google Scholar search engine. The evaluation of the articles was carried out in accordance with the PRISMA recommendations. Based on the search, 4,158 publications were retrieved from PubMed/MEDLINE database, 173 – from eLibrary, and 1,100 publications found with  Google Scholar. After the selection procedure, 121 studies were included in the review.Results. The review provides convincing evidence about a correlation between IM and DRE demonstrating overt differences in IM composition found in patients with epilepsy related to drug sensitivity. IM dysbiosis can be corrected by exogenous interventions such as ketogenic diet, probiotic treatment and fecal microbiota transplantation subsequently resulting in altered brain neurochemical signaling and, therefore, alleviating epileptic activity.Conclusion. A ketogenic diet, probiotics and antibiotics may have some potential to affect epilepsy by correcting IM dysbiosis, but the current studies provide no proper level of evidence. Future clinical multicenter trials should use standardized protocols and a larger-scale patient sample to provide more reliable evidence. Moreover, further fundamental investigations are required to elucidate potential mechanisms and therapeutic targets.